Commercialization and its discontents : companies perspectives - Abu Talib, Noraini (Penerbit UTM, 2008)
Since the late 1990s the government of Malaysia has increased emphasis on its Intensification of Research in Priority Areas (IRPA) program, focusing sc ientific research in universities and government research institutes (GRIs) on activities most likely to enhance national economic performance. The IRPA’s main purpose is to fund commercially viable research for the benefit of business. However, its 2001 mid-term review showed its rates and volumes of commercialization and technology transfer (CTT) to be inadequate. This study aimed to explain the perceived low rate of adoption and commercialization of scientific knowledge in manufacturing in Mala ysia by exploring the actions of companies, universities and GRIs. Two main mo dels of technical change, the Technik and the STH ones, were used. Fieldwork was carried out in Malaysia. Purposive sampli ng led to selection of 60 interviewees: 23 managers and professionals from companies, 17 scientists, eight Technology Transfer Office offi cers, six senior research ad ministrators, three venture capitalists, two journalists and a politic ian. The interviews were open-ended. It was seen that research fi ndings were not always relevant to company interests, and companies often preferred thei r own or adopted, sometimes re verse-engineered, technology. Government CTT funds did not help much in with design, prototypes and pilot plants. Inadequate communication and lack of trust influenced the low uptake of research findings. The commercial relevance of much scientific research was questioned. More government support for company risk-taking appeared to be needed. Differences in attitude and poor understanding of policies and principles tend ed to contribute to low uptake. Managers, professional, scientists, Technol ogy Transfer Officers, senior re search administrators, venture capitalists needed more flexib ility, knowledge and sk ills to respond to profit-driven research findings. A specifically Malaysian approach to CTT was advocated.